Toxicity of dietary Heliotropium circinatum to rats - Eröksüz, H; Eröksüz, Y; Özer, H; Çeribasi, AO; Tosun, F; Tamer, U; Kizilay, ÇA (Comparative Toxicology Lab, 2003)
Pyrrolizidine alkaloid intoxication was produced in adult, male rats by feeding different levels (0, 1. 3, 5 or 10%) of Heliotropium circinatum for 20w. Combined GC-MS revealed 0.15% total alkaloid content in the plant material of which 12% and 88% were basic and N-oxide forms, respectively. The specific alkaloids identified were europine (67.33%), heliotrine (16.34%), lasiocarpine (8.12%), heleurine (4.18%), echinatine (1.56%), 7-angelheliotrine (1.19%), and an unknown alkaloid (1.28%). Neither mortality nor significant clinical changes occurred in test groups. Mild to moderate, dose-related hepatic megalocytosis was the most prominent histopathological finding. In addition to chronic hepatotoxicity, notable media] thickening occurred in the pulmonary arterioles and arteries of the high-dosed groups. This study indicated that H circinatum plant has limited toxic potential in rats with mild to moderate histological changes and no mortality at the dosing levels, total doses, or time of exposure employed.
Keywords: Dolosum Seed; Pyrrolizidine Alkaloids